When academic integrity rules should not apply: a survey of academic staff. Issue 6 (17th August 2021) - Amigud, Alexander; Pell, David J.
Abstract: This study examines circumstances when academic integrity rules may not apply. To this end, we conducted a multinational survey of teaching, research, administrative and support staff ( N = 79). The results suggest that exemptions may be granted on compassionate grounds such as personal welfare, situations where institutional policies are perceived to be unfair or discriminatory, in cases of honest mistakes, and for special activities such as ideological and philosophical debates. Exceptions to academic integrity rules may also be granted to first-time offenders and international students. We argue that inconsistency in policy objectives coupled with differences in staff attitudes, values and beliefs create additional challenges for the implementation of academic integrity measures. However, where policy is perceived to be morally questionable, non-compliance is regarded as an attempt to restore a personal sense of fairness and trust. We further stress that ambiguity of expectations and a disproportionate focus on student action, but not on that of staff, results in an environment where different, and often conflicting, academic integrity practices may operate in parallel leading to even greater inconsistency and procedural unfairness. We discuss the implications and offer recommendations for practice and future research.